Adaptation to the Conditions of the Cyclical Economy as a Tool for Ensuring the Economic Security of the Enterprise - Vasyleha Vadym V. (Bìznes Inform, 2025)
The article is dedicated to the substantiation of the theoretical foundations and approaches to the adaptation of enterprises to the conditions of a circular economy as a tool for ensuring their economic security in the context of transformational changes. It is determined that the circular economy encompasses periods of growth, decline, crisis, and recovery, with each of these stages affecting financial, production, and management processes at the enterprise level differently. It is proved that the economic aspect of adaptation to external conditions aims to enhance the effectiveness of measures focused on the resilience and resource efficiency of the enterprise, which aligns with the key principles of circular development: minimizing losses, optimizing resource use, and maintaining economic integrity. It is noted that the object of adaptive influence is the sphere of the enterprise’s activity that has been most impacted by negative external factors. The conditions for enterprises to adapt to a circular economy are: institutional readiness of the enterprise, innovative transformation of production, risk management under economic instability, energy efficiency, financial sustainability, staffing for adaptation, digitalization, partnership interaction, and integration. It is substantiated that adapting to the external environment within the framework of a circular economy represents a sequential, purposeful, and integrated activity of the enterprise concerning the change of each business element, driven by demand, influenced by scientific and technological progress, and directed towards the existing organizational structure, technological processes, management style and methods, sources of raw materials, markets for goods, and more. Based on this research, adaptation should be understood as a tool for ensuring the economic security of the enterprise, which allows for the timely elimination of internal and external threats through consistent and targeted changes in the activities of the enterprise.